SDUST2023GRA_MSS: the new global marine gravity anomaly model determined from mean sea surface model - Jinyun Guo; Xuyang Wei; Zhen Li; Yongjun Jia; Xiaotao Chang; Xin Liu (Scientific Data)
Abstract The global marine gravity anomalies are primarily recovered from geoid gradients in the along-track directions obtained through satellite altimetry. However, the accuracy of the gravity model is significantly constrained by the sparse geoid gradients in the cross-track directions. To overcome the scarcity of cross-track geoid gradients, we employ a mean sea surface model to calculate geoid gradients in multiple directions, thereby recovering marine gravity anomalies. A global marine gravity anomaly model with 1-arcmin grid was determined from an optimized mean sea surface model. The accuracy of this gravity anomaly model was assessed by shipborne gravity and released marine gravity anomaly models. By the combination of geoid gradients in multiple directions, the meridian components and the prime vertical components of deflections of the vertical achieved consistent accuracy. The accuracy of the gravity anomaly model is 4.31 mGal, derived from shipborne gravity anomalies. Furthermore, the accuracy of this model has been validated across various regions, encompassing different latitudes, bathymetry, and distances from the coastline. The new gravity anomaly model slightly outperforms the released model.